The Lakes-to-the-Gulf Deep Waterway: II - Shelton, William A. (Journal of Political Economy, 1912)
The present movement of freight by water on the Lakes-to-theGulf route is the chief consideration of this chapter. Other writers have shown the decline of river traffic on the Mississippi,' and it appears to be quite well known that the important commerce of former days has disappeared. The question that is uppermost in the minds of those giving thought to transportation on the Mississippi is: Will the river again become an important waterway? The freight movement is discussed for the several sections of the route, beginning at Chicago. Table VIII shows the shipments and receipts of freight at the Port of Chicago for the calendar year I9IO. The lake commerce of the port is divided between the two harbors.2 The iron ore, which comprises approximately one-half the total weight of the shipments and receipts, is discharged almost entirely at the Calumet Harbor; while the general merchandise, the fruits and vegetables, and the lumber come largely to the Chicago Harbor. The lake commerce of Chicago should be important for several reasons. Chicago is located on the route of dense traffic between the seaboard and the West, and the broad open waterway of the